The Influence of Influencer Marketing, Price, And Customer Reviews On Purchasing Decisions for Skintific Products On Shopee - Najib, Ari Syakura; Paramitha, Dyah Ayu (Universitas Nusantara PGRI Kediri, 2025)
Research aim: This study aims to determine whether the variables of influencer marketing, price, and customer reviews have a significant influence on purchasing decisions for Skintific products at Shopee, both partially and simultaneously. Design/Method/Approach: The study used a quantitative approach with a survey method. The population in this study were all students of Universitas Nusantara PGRI kediri who actively use shopee. The sample used in this study was 105 respondents who were taken using purposive sampling technique. The data collection technique used a questionnaire. Data analysis was carried out using multiple linear regression with the help of SPSS software. Research Finding: The results showed that partially, influencer marketing and customer reviews have a significant influence on purchasing decisions, while price does not have a significant effect. But simultaneously, the three variables have a positive and significant influence on purchasing decisions. Theoretical contribution/Originality: This research contributes to the digital marketing literature by emphasizing the importance of influencer marketing and customer reviews as key factors in purchasing decisions, especially on the Shopee platform. Practitionel/Policy implication: The results of this study are expected to help companies, especially Skintific, to optimize their marketing strategies through selecting the right influencers and actively managing customer reviews. In addition, the company is advised to maintain competitive pricing to strengthen its competitiveness in the market. Research limitation: This study is limited to the population of students at Universitas Nusantara PGRI Kediri and Skintific products at Shopee, so the results may not be generalizable. Future research is recommended to expand demographic coverage and add other relevant variables, such as product quality or promotional strategies.